2022
DOI: 10.1002/sce.21754
|View full text |Cite
|
Sign up to set email alerts
|

Exploring factors that impact physical science doctoral student role identities through a multiple case study approach

Abstract: We explore how physical science doctoral students navigate their role identities throughout their graduate programme. Physical science doctoral students take on many academic roles in addition to the role of scientist, including researcher, educator, and student. When social expectations of roles become internalized, they become role identities. We examined doctoral students' academic role identities as a complex system to unpack factors that constrain the behavior and define the nature of doctoral students' a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…al, 2013;Solari & Ortega, 2020), but we offer new insights through a closer examination of how TAs made sense of and negotiated meaning with others and the resulting roles they took up (See Table 2). Extending beyond scholars who have examined specific roles that graduate students take up, such as being a teacher (e.g., Speer et al, 2010) or mentor (e.g., Brown & Sheerin, 2018;McAlister et al, 2022), our study offers a more comprehensive set of roles and dimensions within the TA position and how these roles interact with other positions in a mathematics department, yielding a possible conceptual foundation for continued examination of mathematics graduate students' teacher identity development. Beauchamp and Thomas (2009) wrote that identity "is shaped and reshaped in interactions with others in a professional context" (p. 178), and we found that the instructional context of Math A and the different social relationships led TAs to assume a wide range of role identities, echoing the notion that teachers' identities are multidimensional (e.g., Berger & Lê Van, 2019;Clarke et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…al, 2013;Solari & Ortega, 2020), but we offer new insights through a closer examination of how TAs made sense of and negotiated meaning with others and the resulting roles they took up (See Table 2). Extending beyond scholars who have examined specific roles that graduate students take up, such as being a teacher (e.g., Speer et al, 2010) or mentor (e.g., Brown & Sheerin, 2018;McAlister et al, 2022), our study offers a more comprehensive set of roles and dimensions within the TA position and how these roles interact with other positions in a mathematics department, yielding a possible conceptual foundation for continued examination of mathematics graduate students' teacher identity development. Beauchamp and Thomas (2009) wrote that identity "is shaped and reshaped in interactions with others in a professional context" (p. 178), and we found that the instructional context of Math A and the different social relationships led TAs to assume a wide range of role identities, echoing the notion that teachers' identities are multidimensional (e.g., Berger & Lê Van, 2019;Clarke et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Features of this role encompass practices related to instruction, including preparing and delivering lectures, facilitating discussions, and assessing student performance (e.g., Lee, 2019;Mesa et al, 2014;Speer et al, 2010). Other TA roles include: connecting and building community with and amongst their undergraduate students (Camarao & Din, 2023;Olarte et al, 2021), mentoring (Brown & Sheerin, 2018;McAlister et al, 2022), and supporting peers and undergraduate students (Bowles et al, 2018;Staton & Darling, 1989;Syrnyk, 2018). For example, Brown and Sheerin (2018) described the ways that graduate students enacted different forms of mentorship, ranging from informal mentoring with no set goals or timelines to more formal mentoring.…”
Section: A Myriad Of Rolesmentioning
confidence: 99%
See 2 more Smart Citations